Substituting fossil-based mineral fertilizers with bio-based products - impacts on potentially toxic elements in soil and crops - Salo, Tapio; Keskinen, Riikka; Del Rosario Dominguez Carrasco, Maria; Suomi, Johanna; Ylivainio, Kari (Scientific Agricultural Society of Finland, 2025)
Similar to conventional mineral fertilizers, circular bio-based fertilizer (BBF) products may contain potentially toxic elements (PTEs). In this study, conducted as part of the LEX4BIO project, the contents of arsenic (As), cadmium (Cd), nickel (Ni) and lead (Pb) were surveyed in 37 phosphorus (P) BBFs and 7 nitrogen (N) BBFs representing different product function and component material categories. In addition, mass balances of these elements were calculated over 100-year scenarios of P fertilization with a product that was low or high in the assessed elements, a common mineral phosphate fertilizer (MPF), and a hypothetical fertilizer containing the maximum amount of these PTEs allowed by the EU regulations. The examination was performed using case-specific conditions for Finland, Denmark, France, Spain, Hungary, and Germany, in which countries the products had been tested. Although in some individual products the current maximum EU limits were exceeded for Cd and Ni, the contents of the targeted PTEs were overall low in the studied products. The dominant trends in the contents and fluxes of As, Ni, and Pb were decreasing in all fertilizer-use scenarios with observed BBF concentrations, but the maximum allowed rates would instead commonly lead to prominent increases. The highest sensitivity to variation in fertilizer input rates, along with some substantial increases in the environmental contents and fluxes was observed for Cd. However, with low-Cd BBFs, favorable development is also achievable for Cd fluxes. It is recommended that PTE levels remain well below the maximum EU limits.
Keywords: lannoitteet; raskasmetallit; mass balance modelling; arsenic; cadmium; lead; nickel